A New Tribe of the Ladybird Beetle Subfamily Microweiseinae (Coleoptera: Coccinellidae) Discovered on an Island in the North Atlantic Ocean - Szawaryn, Karol; Větrovec, Jaroslav; Tomaszewska, Wioletta (Insects, 2020)
Microweiseinae is a quite recently established subfamily within ladybird beetles (Coccinellidae). According to recent analyses of morphological and molecular data, it has been divided into three tribes. Members of the subfamily are distributed mostly in tropical and subtropical regions of the world. Despite several recent taxonomical studies of this group, its diversity and distribution is still not fully understood. Recent field collecting on Madeira Island resulted in the discovery of interesting specimens belonging to a yet unknown taxon, described here as Madeirodula atlantica gen. et sp. nov. Phylogenetic analysis of morphological characters indicate that the new taxon form a distinct branch within the subfamily Microweiseinae, for which we propose a new tribe Madeirodulini trib. nov. Evolutionary trends within the subfamily are discussed, and an updated key to the tribes of Microweiseinae is provided.
Keywords: new tribe; Macaronesia; Microweiseinae; Coccinelloidea; new genus; lady beetles; Portugal; Madeira